Linear Transformations of The Basis of The Motivating Word in Russian Inflection and Word Formation (Texas Journal of Multidisciplinary Studies, 2022)
This article describes linear transformations of the stem of a motivating word, which include stem truncation and interfixation. The specificity of these phenomena of Russian word formation is considered from different points of view